2018
DOI: 10.1007/s12149-018-1230-7
|View full text |Cite
|
Sign up to set email alerts
|

Manual on the proper use of lutetium-177-labeled somatostatin analogue (Lu-177-DOTA-TATE) injectable in radionuclide therapy (2nd ed.)

Abstract: Here we present the guideline for the treatment of neuroendocrine tumors using Lu-177-DOTA-TATE on the basis of radiation safety aspects in Japan. This guideline was prepared by a study supported by Ministry of Health, Labour, and Welfare, and approved by Japanese Society of Nuclear Medicine. Lu-177-DOTA-TATE treatment in Japan should be carried out according to this guideline. Although this guideline is applied in Japan, the issues for radiation protection shown in this guideline are considered internationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Since the β-rays of 177 Lu have an average soft tissue range of 0.23 mm which surpasses the cell diameter, an internalization of [ 177 Lu]Lu-PSMA-617 is not necessary for the cell toxicity. Importantly, this enables destroying of surrounding cancer cells which do not express the target (crossfire effect addressing tumor heterogeneity) [ 56 ].…”
Section: Figurementioning
confidence: 99%
“…Since the β-rays of 177 Lu have an average soft tissue range of 0.23 mm which surpasses the cell diameter, an internalization of [ 177 Lu]Lu-PSMA-617 is not necessary for the cell toxicity. Importantly, this enables destroying of surrounding cancer cells which do not express the target (crossfire effect addressing tumor heterogeneity) [ 56 ].…”
Section: Figurementioning
confidence: 99%
“…A Japanese study that measured the exposure dose from patients who had been administered radiopharmaceuticals also indicated that an exposure factor of 0.5 was appropriate [20]. Thus, an exposure factor of 0.5 is used to evaluate the dose for caregivers after a patient is released or discharged [21, 22]. Exposure factor for the general public: 0.25In a typical home, an exposure factor of 0.25 is appropriate based on one study’s measurements of the exposure dose for a patient’s family members [19].…”
Section: Protection From Exposurementioning
confidence: 99%
“…Exposure factor for the general public: 0.25In a typical home, an exposure factor of 0.25 is appropriate based on one study’s measurements of the exposure dose for a patient’s family members [19]. An exposure factor of 0.25 is used for family members other than caregivers and members of the general public after a patient is released or discharged [21, 22]. …”
Section: Protection From Exposurementioning
confidence: 99%
“…Such theranostic procedures are currently attracting attention in nuclear medicine. The implementation of a series of somatostatin receptor imaging and PRRT (peptide receptor radionuclide therapy) for neuroendocrine tumors have proved to be promising, and a large-scale clinical trial of 177 Lu-DOTATATE against neuroendocrine tumors has been conducted (Strosberg and Krenning 2017;Hosono et al 2018), which lead to the approval of the radiopharmaceuticals in 2017 as above. However, imaging with 68 Ga-labeled PSMA ligands and RNT with 177 Lu-labeled PSMA ligands in the management of prostate cancer are currently being conducted at an increasing number of hospitals across the globe.…”
Section: Dosimetry-guided Personalized Therapymentioning
confidence: 99%